An Assessment of the Anaerobic Vial of Paired NR 6A and NR 7N Bactec Blood Cultures - Kevin R Forward; Elizabeth Kerr; Maurice Dalton (Canadian Journal of Infectious Diseases)
Objective: To determine the number of obligate anaerobes recovered in anaerobic blood culture vials and to determine if their recovery had a significant impact on patient care.